A note on the empirical relation between oil prices and the value of the dollar - Jaime R. Marquez; Silvia Merler (Journal of Risk and Financial Management, 2020)
This paper offers an empirical characterization of the relation between the international price of oil and exchange rates that is both useful and reliable. Our characterization is useful because it rests on information of asset prices that are determined in functioning asset markets. Our characterization is reliable because its maintained assumptions are not rejected by the data. Four features differentiate our work from previous analyses. First, our reliance on bilateral rates opens previously ignored financial arbitrage opportunities between oil prices and exchange rates. Second, our emphasis on statistical testing makes our characterization empirically reliable. Specifically, we use a vector-error correction modeling strategy in which both oil prices and exchange rates are endogenous. This framework allows testing for the existence of an arbitrage relation, for the direction of causality, for parameter constancy, for white noise residuals, and for forecast accuracy. Third our reliance on data through 2020 makes our analysis timely. Fourth, to emphasize the advantages of our approach, we compare our results to those derived for formulations relying on effective exchange-rate indexes.
Keywords: 330; real effective exchange rate; China; cointegration; forecasts; oil prices; renminbi